The study on the effects of varying Dopant concentration and Diffusion Time in the design of Silicon Avalanche Diode with minimum Vbr of 120v+20% by simulation - Yip Siew Ling (Universiti Malaysia Perlis, 2008)
Technology CAD (TCAD) refers to the use of computer simulation to model semiconductor processing and device operation. TCAD has two major functions which are process simulation and device simulation. In this project, Synopsys Taurus Workbench including TSUPREM-4 and Medici is used as a virtual IC factory to simulate semiconductor manufacturing processes and predicts device characteristics of an Avalanche diode. The objective of this project is to design of silicon Avalanche diode with minimum breakdown voltage of 120 20% BR V V = ± . The effects of varying doping concentration and diffusion time on the I-V and C-V characteristics are also studied. An Avalanche diode is a silicon diode that is designed to break down and conduct at a specified reverse bias voltage. A common application is in protecting electronic circuits against damaging high voltages. The avalanche diode is connected to the circuit so that it is reverse-biased. If the voltage increases beyond the design limit, the diode suffers avalanche breakdown. Avalanche breakdown is due to impact ionization. Avalanche breakdown is not destructive, as long as the diode is not allowed to overheat. The Avalanche diode is first created using TSUPREM-4. The extraction of electrical characteristics for I-V and C-V is then carried out by using Medici. The effect of different doping concentration of boron and diffusion time on the junction depth j x , reverse breakdown voltage BR V and junction capacitance j C are also studied. From the results, an Avalanche diode of minimum reverse breakdown voltage 120 20% BR V V = ± has been successfully designed. When doping concentration increase, the j x and j C is increase while BR V is decrease. When diffusion time increase, the j x and j C is increase while BR V is decrease.